English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-07 21:08:01 · 5 answers · asked by Thomas and M 1 in Science & Mathematics Mathematics

5 answers

-18/x^2 + 2x - 24

2006-12-07 21:14:09 · answer #1 · answered by Anonymous · 0 0

provided that you meant:

(6x-3)/(x^2-x-12) - (2x-15)/(x^2-x-12)

answer:
[(6x-3) - (2x-15)]/(x^2-x-12)=
= (6x-3-2x+15)/(x^2-x-12)
= (4x+12)/(x^2-x-12)

factor both numerator and denominator:
4x+12 = 4(x+3)

x^2-x-12 = x^2-4x + 3x -12
= x(x-4) + 3(x-4)
= (x-4)(x+3)

plug them into your expression:
4(x+3)
over
(x-4)(x+3)

cancel (x+3) in both numerator and denominator
4/(x+4)

this is the solution

2006-12-08 01:15:35 · answer #2 · answered by Mirta G 2 · 0 0

very easy, the denominator of the 2 fractions are the same so you have only to add numerators and divide by the common denominator

answer 4x-18/x^2-x-12
the denominator is(x4)-3 )( x+4)

so 2(x-9)/(x-3) (x+4)

2006-12-07 21:28:22 · answer #3 · answered by maussy 7 · 0 0

if its (6X - 3)/(X^2-X-12) - (2X-15)/(X^2-X-12);

(X^2-X-12) = (X-4)*(X+3)

(6X - 3)/(X^2-X-12) - (2X-15)/(X^2-X-12)
= {(6X - 3) - (2X-15)}/{(X-4)*(X+3)}
= {4X + 12}/{(X-4)*(X+3)}
= 4(X+3)//{(X-4)*(X+3)}
= 4/(X-4)

2006-12-07 21:24:36 · answer #4 · answered by nalaka 2 · 0 0

-18/X^2 +2X-24

2006-12-07 21:17:15 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers